2021
DOI: 10.1016/j.chemgeo.2021.120444
|View full text |Cite
|
Sign up to set email alerts
|

The significance of galena Pb model ages and the formation of large Pb-Zn sedimentary deposits

Abstract: In an attempt to clarify the significance of Pb model ages in Pb-Zn sedimentary deposits, we report high-precision Pb isotopic compositions for 64 galenas and 52 K-feldspars, the former from ores and the latter separated from granites. All samples are from Spain and the French Pyrenees. Lead from galena ores is of unequivocal continental origin. With few exceptions, Pb model ages systematically exceed emplacement ages by up to 400 Ma, a gap which is well outside the uncertainties of ~30 Ma assigned to the mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 138 publications
(166 reference statements)
0
8
0
Order By: Relevance
“…The Proterozoic-Cambrian metallogeny, developing with many lead-zinc deposits and lead-zinc occurrences as lead-zinc ore fields in the Du Tien, Lung Dam, Ta Pan, Ban Bo, Ban Lin-Lung Thom, and Phieng Phat deposits, are presented in Eldridge et al 1988, Kerridge et al 1988, and Naylor et al 1989 of the imperfect mixing of normal lead in different source regions. Therefore, it is pointed out from the above Pb isotopic composition characteristics that the lead sources are not only the lower crust but also some other source regions, for example, the basement of the Caledonian and Yanshanian orogenic zones (Velasco et al 1996, Golonka et al 2006, Hoa et al 2008, Hung 2010, Milot et al 2021. From these diagrams, it can be seen that there has been an evolution of the material supply sources gradually shifting to the deep sources of the lower crust and forming in the orogenic settings.…”
Section: Sulfur and Lead Isotope Compositionsmentioning
confidence: 97%
“…The Proterozoic-Cambrian metallogeny, developing with many lead-zinc deposits and lead-zinc occurrences as lead-zinc ore fields in the Du Tien, Lung Dam, Ta Pan, Ban Bo, Ban Lin-Lung Thom, and Phieng Phat deposits, are presented in Eldridge et al 1988, Kerridge et al 1988, and Naylor et al 1989 of the imperfect mixing of normal lead in different source regions. Therefore, it is pointed out from the above Pb isotopic composition characteristics that the lead sources are not only the lower crust but also some other source regions, for example, the basement of the Caledonian and Yanshanian orogenic zones (Velasco et al 1996, Golonka et al 2006, Hoa et al 2008, Hung 2010, Milot et al 2021. From these diagrams, it can be seen that there has been an evolution of the material supply sources gradually shifting to the deep sources of the lower crust and forming in the orogenic settings.…”
Section: Sulfur and Lead Isotope Compositionsmentioning
confidence: 97%
“…Iberia was the major source of silver for the Carthaginian and Roman worlds up until the 2 nd century A.D., and Pb isotope data on potential silver ores are extremely well documented (see García de Madinabeitia et al, 2021, and references therein). Therefore, we measured Ag isotopes and trace element abundances on the galena sample suite documented for Pb isotopes by Milot et al (2021a) to identify which of these Iberian Pb ores may have actually been mined for use of their silver in minting Roman denarii.…”
Section: National Institute Of Standards and Technologymentioning
confidence: 99%
“…Geological information on the galena samples analyzed here is summarized by Milot et al (2021a), and further details can be found in the IBERLID database (García de Madinabeitia et al, 2021; http://www.ehu.eus/ibercron/ iberlid). Briefly, most deposits of economic importance are located in the southern part of the Iberian Peninsula (see the Supplemental Material 1 ).…”
Section: Potential Iberian Sources Of Roman Lead and Silvermentioning
confidence: 99%
“…Europe, colonial Spanish Americas) is extremely narrow (ε 109 Ag = 1 to +1; Desaulty et al, 2011;Desaulty and Albarède, 2013;Albarède et al, 2016Albarède et al, , 2021; Hacksilber from the ancient southern Levant: ε 109 Ag = 2 to +1; Eshel et al, 2022), the range is much broader for silver ores (-8 to +9; Mathur et al, 2018;Arribas et al, 2020;Wang et al, 2022) and for Iberian galena samples (ε 109 Ag = 8 to +3; Milot et al, 2021a). This stark contrast offers the potential to differentiate Ag-bearing ores that actually may have produced metal used for coinage from other mines which did not contribute to coin production.…”
mentioning
confidence: 99%
“…The companion Pb isotopic compositions are published and discussed in Vaxevanopoulos et al (2022). We also tested whether sulfur isotopes provide a means for ore source discrimination or offer any other insight into the petrological processes of silver ore formation by measuring  34 S on a subset of the Aegean ores investigated by Vaxevanopoulos et al (2022) and the Iberian galena samples for which Ag and Pb isotopes are published by Milot et al (2021aMilot et al ( , 2022.…”
mentioning
confidence: 99%